Development and Comparison of DDS and Multi-DDS Chirp Waveform Generator - Kim, Kyeong Rok; Kim, Song; Ki, Choong Ho; Kim, Tu Hwan; Yang, Heein; Kim, Jae Hyun (International Geoscience and Remote Sensing Symposium (IGARSS), 2019)
A synthetic aperture radar (SAR) is electromagnetic equipment which is composed of digital parts. It transmits and receives microwaves for observing long distance. In digital system, system clock is an important factor that determines waveform resolution. The SAR system is consist of FPGA, DAC, and other digital parts. In the SAR system, clock of FPGA and DAC are an upper limit for generation of chirp signal. However, digital parts are mostly expensive due to its specification. In this paper, we develop two types of digital waveform generator and propose a method for chirp waveform generation using relatively low cost parts. We test the chirp waveform generators. One used Virtex-5 and one DDS, and the other used Kintex-7 and four DDSs. In addition, we compare the waveform quality using impulse response function. As a results, peak to side-lobe ratio is -14.68 dB and -11.54 dB, and integrated side-lobe ratio is -21.78 dB and -15.48 dB, relatively.
Keywords: chirp; Chirp waveforms; Digital parts; Digital system; Digital waveform generators; Impulse response functions; multi-DDS; Waveform quality; chirp; FPGA; IRF; multi-DDS; SAR